PENINGKATAN KETERAMPILAN KELUARGA DALAM PENCEGAHAN GANGGUAN PERTUMBUHAN BATITA - Aswati; Agus Supinganto; Sopian Halid; Melati Inayati Albayani; Henny Yolanda; Winda Nurmayani (Stikes Yarsi Mataram, 2023)
Indicators of community nutrition development through nutrition management in toddlers need to be supported by the family's ability to recognize children's growth. Having a healthy child is the hope of all families. To achieve this, of course, the family must be able to carry out family care functions which include, getting to know, making the right decisions, caring for, providing a supportive environment and utilizing existing health facilities. The purpose of this community service is to improve the ability about the function of family care in the prevention of toddler growth disorders. The outputs resulting from this community service are educational videos on preventing toddler growth disorders and the toddler growth module.